Bacteriological profile of patients with biliary obstruction in tertiary care center - Parappanavar, Neelakanth U.; Suman, Sumit Kumar; Katepally, Sai Krishna; Kumar, P. Shravan; Singh, Prafulla Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Bile ducts are usually kept sterile by bacteriostatic and flushing effects of bile. Patients presenting with biliary obstruction especially due to benign etiology have either single or multiple bacterial organisms. Acute cholangitis carries significant morbidity with variable mortality rate. The serious presentation of such toxic patients signifies the requirement of appropriate antibiotic treatment. Choledocholithiasis followed by neoplasm and benign biliary strictures are the common predisposing factors for obstruction. Widespread use of antibiotics over years lead to change in sensitivity pattern of organisms which necessitates change in empiric antibiotic usage. Methods: This retrospective study was conducted in department of medical gastroenterology. We studied 50 patients with biliary obstruction (clinical and demographic data were recorded). The diagnosis of cholangitis was made according to TG2018. While undergoing therapeutic ERCP, bile aspirate was collected by biliary cannulation and sent for microbiological analysis. The antibiotic susceptibility pattern and rest of the data were analyzed by appropriate statistical tests. Results: Mean age of the study group was 49 years. Majority were female in study (60%). Overall, 74% had benign etiology, 32% had cholangitis. Bile cultures were positive in 64% patients 75% of them had benign etiology (gallstone being most common; 56%) and 25% had malignant etiology. Bacterobilia in cholangitis patients was statistically significant in comparison to patients without cholangitis (p-0.01). Organisms grown are mainly aerobic gram negative, most common being E. coli, Klebsiella and Pseudomonas species. Patients having bacterobilia had mortality of 6.25% during hospital stay. Conclusions: In this study we found higher sensitivity to colistin (90.6%), tigecycline (81.25%), amikacin (75%) and least sensitivity was noted for ampicillin (6.25%) followed by cefixime (12.5%). Sensitivity to previously commonly used ciprofloxacin antibiotic was 31.25%. Study confirms the significance of obtaining routine bile sample during ERCP in obstructed biliary system to prevent dreaded complications of cholangitis.